Depletion of endogenous germ cells in striped catfish Pangasianodon hypophthalmus (Sauvage, 1878) by heat–chemical treatments. Issue 12 (26th September 2019) - Majhi, Sullip Kumar; Maurya, Pradip Kumar; Kumar, Santosh; Mohindra, Vindhya; Lal, Kuldeep Kumar
Abstract: Germ cell (GC) transplantation (GCT) is a proven powerful reproductive technique to enhance the production efficiency of domesticated animals and aid to the recovery of endangered germ lines. In mammals, several methods have been adopted for the eradication of GCs such as treatment with cytotoxic drugs, irradiation, cold ischaemia and hyperthermic treatment. Some of these methods have also been tried in fishes, and conditions for sterilization of gonads have been established. Here, we report the production of GC‐depleted male striped catfish Pangasianodon hypophthalmus in 12 weeks by the combination of heat and chemical treatments. The cytotoxic drug busulphan (40 mg/kg) was intraperitoneally injected into the animals at 2‐week intervals (six doses in total) and maintained in water at 38°C between weeks 1 and 12. The effectiveness of the treatment was assessed using gonadal index and histology. At the end of 12 weeks, very severe gonadal degeneration was observed in fish treated with the heat–chemical combination, and 100% of sampled fish ( n  = 5) were found devoid of endogenous GCs. On contrary, high temperature alone caused minor gonadal degeneration. Results obtained in this study suggest that endogenous GCs of large‐bodied fish such as P. hypophthalmus can also be sterilized by heat and chemical treatments within a considerably short period.